Mapping Communication Priority of Local Government Leaders through Instagram Captions in Publicising Smart City Programmes - Anggadwita, Grisna; Alamanda, Dini Turipanam; Permatasari, Anggraeni; Setiawan, Idzhar Inzaghi (School of Business and Management Institut Teknologi Bandung, 2021)
Currently, social media is required to inform the public about local government programmes related to smart city. Advances in technology require the government to provide fast, precise and accurate information services. Local government leaders' communication patterns are crucial factors in the successful implementation of the smart city technology. This study aims to map the communication priorities of DKI Jakarta government leaders in publicising the smart city programmes using Instagram. The study, using a qualitative method with a content analysis approach, employs a case study involving an Instagram account owned by Anies Baswedan as the head of the DKI Jakarta regional government, analysing captions posted between February 2019 and February 2020. The ATLAS.Ti program was used for data processing. The study results reveal that the highest priority area for communication regarding the smart city programmes was Smart Economy. Moderate priorities included Smart Living, Smart People, Smart Governance and Smart Mobility. Lastly, Smart Environment had a low priority. This study demonstrates that Instagram can be an effective medium for building interaction between leaders and the community in delivering smart city programmes with balanced communication intensity for each programme. Thus, this study's findings are expected to provide a reference for local government leaders in balancing communication priorities for all smart city programmes.